2011
DOI: 10.3109/0284186x.2010.547217
|View full text |Cite
|
Sign up to set email alerts
|

HER2status in operable breast cancers from Vietnamese women: Analysis by immunohistochemistry (IHC) and automated silver enhancedin situhybridization (SISH)

Abstract: HER2 gene amplification was found in 41% of Vietnamese breast cancers; this level is considerably higher than that previously found in a series of Swedish breast cancer women. The HER2-positive tumors were more often found in post-menopausal women than in ER negative tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 159 publications
(284 reference statements)
3
9
0
Order By: Relevance
“…In the present study, there was seen significant correlation between age of the patient and ER (p value=0.000), PR (p value=0.000) and HER2/neu (p value=0.000) expression in present study. Studies by Desai SB et al, [28] Dodiya H et al, [29] Thang VH et al, [30] and Ganesan M et al, [31] showed similar results. The majority of receptors positive cases were postmenopausal in our study.…”
Section: Subtype4mentioning
confidence: 53%
“…In the present study, there was seen significant correlation between age of the patient and ER (p value=0.000), PR (p value=0.000) and HER2/neu (p value=0.000) expression in present study. Studies by Desai SB et al, [28] Dodiya H et al, [29] Thang VH et al, [30] and Ganesan M et al, [31] showed similar results. The majority of receptors positive cases were postmenopausal in our study.…”
Section: Subtype4mentioning
confidence: 53%
“…HER2/neu oncogene codes the trans-membrane protein that has tyrosine kinase activity (Thang et al, 2011). HER2/Neu (cerbB2), a member of the epidermal growth factor receptor family, which plays an important role in breast cancer pathogenesis, is localized in the long arm of the 17 th chromosome (17q11.2-q12).…”
Section: Discussionmentioning
confidence: 99%
“…The response to herceptin treatment is directly related to the HER2 status of the patient (Dietel et al, 2007;Thang et al, 2011). Therefore, it is imperative to identify the method that defines the HER2 status with the greatest safety; this issue remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations